The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2005
DOI: 10.1146/annurev.psych.55.090902.142023
|View full text |Cite
|
Sign up to set email alerts
|

Vestibular, Proprioceptive, and Haptic Contributions to Spatial Orientation

Abstract: The control and perception of body orientation and motion are subserved by multiple sensory and motor mechanisms ranging from relatively simple, peripheral mechanisms to complex ones involving the highest levels of cognitive function and sensory-motor integration. Vestibular contributions to body orientation and to spatial localization of auditory and visual stimuli have long been recognized. These contributions are reviewed here along with new insights relating to sensory-motor calibration of the body gained … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
146
0
6

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 231 publications
(160 citation statements)
references
References 113 publications
5
146
0
6
Order By: Relevance
“…Similar responses were observed following injection of anaesthetic into cervical structures, surgical sectioning of cervical nerves (De Jong, De Jong, Cohen, & Jongkees, 1977) and the development of fatigue in cervical musculature (Gosselin et al, 2004;Stapley et al, 2006;. These disturbances in postural control are thought to result from the mismatch that is created between visual, vestibular and somatosensory input which then interferes with the estimation of body orientation In order to form useful kinaesthetic sensation the CNS must be able to interpret the proprioceptive signals within the reference framework provided by the internal schema of the 24 body (Lackner & DiZio, 2005). The effect of altered proprioceptive input on this internal map is illustrated by the 'Pinocchio' illusion.…”
Section: Pain-induced Impairment Of Proprioceptive Functionmentioning
confidence: 99%
“…Similar responses were observed following injection of anaesthetic into cervical structures, surgical sectioning of cervical nerves (De Jong, De Jong, Cohen, & Jongkees, 1977) and the development of fatigue in cervical musculature (Gosselin et al, 2004;Stapley et al, 2006;. These disturbances in postural control are thought to result from the mismatch that is created between visual, vestibular and somatosensory input which then interferes with the estimation of body orientation In order to form useful kinaesthetic sensation the CNS must be able to interpret the proprioceptive signals within the reference framework provided by the internal schema of the 24 body (Lackner & DiZio, 2005). The effect of altered proprioceptive input on this internal map is illustrated by the 'Pinocchio' illusion.…”
Section: Pain-induced Impairment Of Proprioceptive Functionmentioning
confidence: 99%
“…The observation that visuotactile stroking in the present conditions does not modulate the subjective 1PP raises the question which combinations of multisensory visual-tactilevestibular stimulus combinations most strongly affect the subjective 1PP. Previous behavioral and psychophysics studies have provided evidence that the perception of the spatial orientation of the own body in space is affected, for instance, by footsole pressure (Lackner 1992;Lackner and DiZio 2000), neck-muscle vibration (Lackner and DiZio 2005), large-field optokinetic stimulation (De Saedeleer et al 2013), or static tilts of the visual environments (Tiliket et al 1996). These multisensory effects on spatial perception suggest that similar stimulations may also impact spatial aspects of BSC, in particular the subjective 1PP.…”
Section: Subjective 1pp: No Modulation By Visuotactile Strokingmentioning
confidence: 99%
“…Tactile stimuli can also modify ongoing perceptions of orientation and self-motion (Lawson, Rupert, Guedry, Grissett, and Mead, 1997;Lackner and DiZio, 2005). For example, Lackner and Graybiel (1978) reported that somatosensory stimuli systematically altered vestibular illusions of motion associated with off-vertical rotation and perceptions of self orientation during the weightless phases of parabolic flight.…”
Section: Introductionmentioning
confidence: 99%